Communication in children and adolescents after acquired brain injury: An exploratory study - Åsa Fyrberg; Göran Horneman; Jakob Åsberg Johnels; Gunilla Thunberg; Elisabeth Ahlsén (Medical Journals Sweden, 2017)
Objective: The usability of the Communicative Effectiveness Index (CETI) in adolescents with acquired brain injury was investigated and compared with linguistic, cognitive and brain injury data. Design: A prospective, longitudinal, between-group design. Subjects: Thirty participants were divided into 2 subgroups: CETI+ and CETI− groups. Methods: Parental CETI ratings of daily communication were compared with linguistic data and IQ test results. Lesion site and aetiology were also studied. Results: The CETI+ group (n = 16) had a mean score greater than 75 out of 100, while the mean score of the CETI− group (n = 14) was below 75. Complex daily communication was impaired in both groups, but the CETI− group scored significantly lower on verbal IQ and grammar comprehension tests and had more naming difficulties. A majority of subjects in the CETI− group had a left hemisphere injury. Traumatic vs non-traumatic acquired brain injury did not differentiate the results.  Conclusion: Specific complex CETI items provided unique information that is not easily measured by linguistics and cognitive tests for use with the acquired brain injury group. Parental evaluations of communication skills were well reflected in language and verbal IQ test results. Left hemisphere injury was associated with poorer communication outcome.